Narrating in Cooperative Learning Integrated Reading and Composition (CIRC) Learning in Elementary School to Improve Reading Skills - Artawan, Gde (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The current real condition in Indonesia, reading has not become a daily culture of society, especially for the students. For the students, reading is not something fun to be done even on the contrary it becomes something boring and saturating. This study aimed at examining the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by a fairytale toward students' reading skills. This study was a quasi-experimental study designed in a non-equivalent post-test only control group. The population of this study was 98 students. The sample of this study was the fifth grade of Kaliuntu 3 Elementary School, with 23 students and the fifth grade of Kaliuntu 2 Elementary School with 18 students, determined by random sampling technique. Reading skill test in the form of an objective test of 25 questions was used as the instrument. The obtained data were analyzed using inferential statistical analysis (t-test). Based on the results of the t-test calculation, tcount was greater than ttable (tcount 4.31> ttable 2.042) so H0 was rejected and Ha was accepted. It means that there are significant differences in reading skills between the groups of students who are taught using Cooperative Integrated Reading and Composition (CIRC) learning models assisted by fairy tales and the groups of students who were taught using conventional learning. Based on the average value it was known that the average value of the experimental group was greater than the control group. Thus, it can be concluded that the fairytale assisted Cooperative Integrated Reading and Composition (CIRC) learning model has a positive effect on students' reading skills in elementary school students. This finding will have implications that is, to improve students' reading skills at the elementary school can be done by using a CIRC learning model assisted by fairy tales assisted by fairy tales.